Continuous pressurized extraction versus electric fields-assisted extraction of cyanobacterial pigments - Pagels, Fernando (2021)
Cyanobacteria pigments, in special carotenoids and phycobiliproteins, are usually used in industry as raw extracts, although there is still no standard methodology for their extraction. For the co-extraction of carotenoids and phycobiliproteins from the marine cyanobacterium Cyanobium sp., a continuous pressurized solvent extraction (CPSE) system and an electric fields-assisted extraction system based in ohmic heating were optimized using Central Composite Designs, with three factors each: time (t), temperature (T) and, flow (f) for CPSE; and time, temperature and frequency (F) for ohmic heating. The content of pigments and the antioxidant capacity of extracts were evaluated. All tested factors seem to influence the extraction of pigments in different ways: a high temperature (70 °C) had a positive impact on the extraction rate in both methods, while the influence of time depended on the extraction principle. Flow and frequency affected directly the extraction efficiency and these methods are indeed suitable for cyanobacterial pigments extraction, achieving good extraction results. Optimal conditions for co-extraction of carotenoids and phycobiliproteins in CPSE were T=70 °C, t=20 min and f=1.5 mL min1, and for ohmic heating they were T=70 °C, t=5 min and F=20 kHz. Both, CPSE and ohmic heating systems allowed obtaining better extraction yields when compared with a previously optimized extraction method (homogenization), used here as a reference. However, ohmic heating was the best methodology for pigments co-extraction from Cyanobium sp.